Conformational Modulation of Iduronic Acid‐Containing Sulfated Glycosaminoglycans by a Polynuclear Platinum Compound and Implications for Development of Antimetastatic Platinum Drugs. (9th December 2020) - Gorle, Anil K.; Haselhorst, Thomas; Katner, Samantha J.; Everest‐Dass, Arun V.; Hampton, James D.; Peterson, Erica J.; Koblinski, Jennifer E.; Katsuta, Eriko; Takabe, Kazuaki; von Itzstein, Mark; Berners‐Price, Susan J.; Farrell, Nicholas P.
Abstract: 1 H NMR spectroscopic studies on the 1:1 adduct of the pentasaccharide Fondaparinux (FPX) and the substitution‐inert polynuclear platinum complex TriplatinNC show significant modulation of geometry around the glycosidic linkages of the FPX constituent monosaccharides. FPX is a valid model for the highly sulfated cell signalling molecule heparan sulfate (HS). The conformational ratio of the 1 C 4 : 2 S 0 forms of the FPX residue IdoA(2S) is altered from ca. 35:65 (free FPX) to ca. 75:25 in the adduct; the first demonstration of a small molecule affecting conformational changes on a HS oligosaccharide. Functional consequences of such binding are suggested to be inhibition of HS cleavage in MDA‐MB‐231 triple‐negative breast cancer (TNBC) cells. We further describe inhibition of metastasis by TriplatinNC in the TNBC 4T1 syngeneic tumour model. Our work provides insight into a novel approach for design of platinum drugs (and coordination compounds in general) with intrinsic anti‐metastatic potential. Abstract : A novel approach for the design of platinum complexes with intrinsic anti‐metastatic potential is presented. Metalloshielding of a model heparan sulfate (HS) pentasaccharide by the highly cationic TriPlatinNC modifies the conformational preference of the critical iduronic acid residue. Structural modulation of HS can result in inhibition of cellular cleavage by hepara(i)nase with a consequence in tumour cells being prevention of metastases.